INDOLBUTIRIC ACID IN ROOTING SEMIHARDWOOD CUTTINGS OF DELLA NONA AND ELDORADO PEACH CULTIVARS - RIBAS, Claudinei Pedroso; GOMES, Felipe Gonçalez Dias; LEONOR, Rosimeri; BIASI, Luiz Antônio; MARÇALLO, Francisco Antonio (Scientia Agraria, 2007)
The peach propagation in Brazil is based on grafts on seedlings rootstocks. The cutting of scion could be used to obtain better uniform plants. The objective of this paper was to evaluate the effect of the indolbutiric acid (IBA) in root cuttings of Della Nona and Eldorado peach cultivars. The experiment was carried out in a greenhouse with intermitent mist, from April until June 2006. The cuttings were collected from two-year-old stock plants prepared with 15 cm of length and 4 leaves cut in the middle. The experimental design was completely randomized with six reapplications and 16 cuttings per plot. The treatments were the following concentrations of IBA: 0, 1000; 2000; and 3000 mg L-1. The experiment was evaluated after 73 days. The percentage of root cuttings was increased with IBA concentrations, whose greatest rates were estimated by an equation of regression and were 73% and 33% of rooting with the 1838 mg L-1 and 1666 mg L-1 IBA concentrations to Della Nona and Eldorado, respectively. The IBA also promoted the root growth to cultivate ‘Della Nona’, with greater length (9,76 cm with 1812 mg L-1 of IBA) and greater number of roots (7,5 with 3000 mg L-1 of IBA). It is concluded that the Della Nona cultivars have potential to be propagated by semihardwood cuttings with IBA application.